PTH-010 Outcomes After Use of Patency Capsules Prior to Video Capsule Endoscopy. (17th August 2016) - Bond, A; Collins, P
Abstract : Introduction: Capsule retention is an important complication in patients attending for video capsule endoscopy (VCE). It may necessitate endoscopic, surgical or medical intervention. Successful passage of a Patency capsule (PC) predicts the safe passage of the video capsule in the majority of patients with a high risk of stricturing disease. The PC disintegrates after 30 h exposure to GI secretions. It contains a radiofrequency tag that can be detected by a hand-held scanner. Its position in the gastrointestinal tract may be misinterpreted if plain abdominal X-ray is used to assess the position of the PC. Its position can be reliably detected by a limited, targeted CT scan. This strategy has been associated with a requirement for targeted CT scan in 46% of patients attending for PC. 1 Methods: This was a retrospective observational study performed in a tertiary referral centre. Data was collected on all patients undergoing patency capsule from July 2013 to October 2015, at the Royal Liverpool University Hospital. Patients attended the hospital 30 hours after ingestion of the PC. Patients with a PC detected by hand-held scanner underwent a targeted, limited CT scan to identify the position of the capsule. Patients were referred for VCE if the PC had passed into the colon. Results: 101 patients underwent investigation with PC. The commonest indication for a patency capsule test was known or suspected IBD in 22/101 and 54/101 patients, respectively. 55 / 101 patients required a low dose CT scan to identify the site of PC within the GI tract. 10 of 101 patients failed to achieve passage of the PC (9.9%). 9/10 patients had suspected or known small bowel Crohn's disease. 4/9 patients had undergone prior small bowel imaging. (3 MR small bowel examinations and one barium study.) One MR scan had suggested a possible short stricture, but with no pre-stenotic dilatation to suggest functional obstruction. Of the remaining 91 patients, 76 had VCE examination. In 8 (10.5%) examinations, the capsule failed to reach the caecum within the recording period. In all 8, the capsule subsequently passed. 42 of the 76 VCE examinations were reported as normal. Conclusion: 54% of patient attending PC required a targeted low dose CT scan to identify the site of the PC in the GI tract. Suspected or known small bowel Crohn's disease is a risk for failure of the PC to leave the small bowel. Small bowel imaging does not reliably predict successful passage of the PC which correlates with previous reports indicating that normal small bowel imaging may not exclude lesions that cause retention of the video capsule. No capsule retentions were identified in patients with a successful patency test, supporting its use as a test in patients with clinical characteristics that increase concerns for capsule retention. Reference: 1 Assadsangabi A, et al . J Gastroenterol Hepatol . 2015;30 (6):984–9 Disclosure of Interest: None Declared